Analysis of Bank Health Level at PT Bank Central Asia Tbk Based on the RGEC Method for the 2015-2019 Period - Nofiana, Lina; Yunanti, Siska; Amelia, Rizka Wahyuni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine the level of Bank Soundness at PT Bank Central Asia Tbk based on the RGEC method for the period 2015 – 2019 which is recorded in Indonesia Stock Exchange (IDX). The data analysis method uses the RGEC approach, collecting data that relating to the component indicators of the RGEC method and related data with the results of self assessment, calculating the indicator value of each components of the RGEC method in accordance with Bank Indonesia regulation No.13/1/PBI/2011 and Circular Letter of the Financial Services Authority No. 14/SEOJK.03/2017. The results of research at PT. Bank Central Asia Tbk 2015 period predicate Bank Central Asia's soundness rating is “VERY HEALTHY”, with a score of weighting of 93.33%, in 2016 the predicate of the soundness of Central Bank Asia “VERY HEALTHY”, with a weighted score of 96.67%, in 2017 Bank Central Asia's rating of "HEALTH" level of soundness, with a weighting score of by 93.33%, in 2018 the predicate of Bank Central Asia's soundness level “HEALTH”, with a weighting value of 93.33%, in 2019 the predicate level of Bank Central Asia (BCA) “HEALTH”, with a weighting value of 96.67%. And in general for the 2015-2019 period the Bank's soundness level Victoria is at the “HEALTH” level with an average weighting value of 94.67%.